The intrinsically disordered structural platform of the plant defence hub protein RPM1‐interacting protein 4 provides insights into its mode of action in the host‐pathogen interface and evolution of the nitrate‐induced domain protein family. (8th August 2014) - Sun, Xiaolin; Greenwood, David R.; Templeton, Matthew D.; Libich, David S.; McGhie, Tony K.; Xue, Bin; Yoon, Minsoo; Cui, Wei; Kirk, Christopher A.; Jones, William T.; Uversky, Vladimir N.; Rikkerink, Erik H. A.
<x xml:space="preserve">Abstract</x> Arabidopsis thaliana (At) RPM1‐interacting protein 4 (RIN4), targeted by many defence‐suppressing bacterial type III effectors and monitored by several resistance proteins, regulates plant immune responses to pathogen‐associated molecular patterns and type III effectors. Little is known about the overall protein structure of AtRIN4, especially in its unbound form, and the relevance of structure to its diverse biological functions. AtRIN4 contains two nitrate‐induced (NOI) domains and is a member of the NOI family. Using experimental and bioinformatic approaches, we demonstrate that the unbound AtRIN4 is intrinsically disordered under physiological conditions. The intrinsically disordered polypeptide chain of AtRIN4 is interspersed with molecular recognition features (MoRFs) and anchor‐identified long‐binding regions, potentially allowing it to undergo disorder‐to‐order transitions upon binding to partner(s). A poly‐l‐proline II structure, often responsible for protein recognition, is also identified in AtRIN4. By performing bioinformatics analyses on RIN4 homologues from different plant species and the NOI proteins from Arabidopsis, we infer the conservation of intrinsic disorder, MoRFs and long‐binding regions of AtRIN4 in other plant species and the NOI family. Intrinsic disorder and MoRFs could provide RIN4 proteins with the binding promiscuity and plasticity required to act as hubs in a pivotal position within plant defence signalling cascades.